Zróżnicowanie europejskiej przestrzeni regionalnej w świetle koncepcji gospodarki opartej na wiedzy - Markowska, Małgorzata (Diversification of European Regional Space at the Background of Knowledge Based Economy Concept, 2007)
The article is an attempt to identify knowledge based economy in European regions and an assessment of the European regional NUTS 2 level space diversification. 240 European regions underwent the analysis in which in order to describe knowledge based economy there were used five variables illustrating the share of employed university graduates in the overall population number aged 25-64, the share of population participating in continuing education in the total population number aged 25-64, the number of patents per 1 million of labour force, the share of workers employed in services "based on knowledge", the share of mid- and high-tech industry employees. The research conducted facilitated an assessment of the level of regional diversification in EU countries with reference to selected knowledge based economy identifiers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 35-48